2001
DOI: 10.1002/chin.200135072
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: cis‐Selective Asymmetric Cyclopropanation of Olefins Catalyzed by Five‐Coordinate [RuCl(PNNP)]+ Complexes.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Ruthenium complexes with tetradentate PNNP ligands are active catalysts for a variety of enantioselective reactions, including hydrogenations and transfer hydrogenations of ketones, 75 epoxidations of olefins, 76 Diels−Alder reactions, 77 and cyclopropanations. 78 Saudan et al 15 reported that the Ru− 1) is active for ester hydrogenations (0.05 mol % 1, 5 mol % NaOMe, 100 °C, 49 atm H 2 , THF, 1 h, TON = 1980). Although 1 does not contain N−H groups, it is quite reasonable to expect that the imine groups are reduced to the corresponding amines during the initial stages of the hydrogenation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Ruthenium complexes with tetradentate PNNP ligands are active catalysts for a variety of enantioselective reactions, including hydrogenations and transfer hydrogenations of ketones, 75 epoxidations of olefins, 76 Diels−Alder reactions, 77 and cyclopropanations. 78 Saudan et al 15 reported that the Ru− 1) is active for ester hydrogenations (0.05 mol % 1, 5 mol % NaOMe, 100 °C, 49 atm H 2 , THF, 1 h, TON = 1980). Although 1 does not contain N−H groups, it is quite reasonable to expect that the imine groups are reduced to the corresponding amines during the initial stages of the hydrogenation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The complexity of these catalysts 7,8 highlights the challenge to kinetically favor cis-cyclopropanes over their more stable trans diasteroisomers. Desirable catalytic approaches only offer limited scope 9 or low diastereo-and enantioselectivity. 10 In particular, the cis-cyclopropanation of alkenes employing benzylidenes is still problematic, due to the instability of the phenyldiazomethane precursors and the difficult taming of the resulting reactive intermediates.…”
mentioning
confidence: 99%
“…To further explore the synthetic potential of this system, we obtained a cis-cyclopropane-modified phenylalanine amino acid (4u) in two steps from commercially available 4-iodophenylalanine. Moreover, the asymmetric total synthesis of the combretastatin A4 analogue 4v 6a was achieved in three steps starting from isovanillin (9) in 39% overall yield (Scheme 2B). To put these results in perspective, twice as many steps (including a resolution) were previously required to obtain this product in <10% overall yield from comparable materials.…”
mentioning
confidence: 99%